Circulating tumor DNA reveals complex biological features with clinical relevance in metastatic breast cancer - Aleix Prat; Fara Brasó-Maristany; Olga Martínez-Sáez; Esther Sanfeliu; Youli Xia; Meritxell Bellet; Patricia Galván; Débora Martínez; Tomás Pascual; Mercedes Marín-Aguilera; Anna Rodríguez; Nuria Chic; et al. (Nature Communications, 2023)
Plasma ctDNA is a promising method to determine patient outcome in multiple cancer types. Here, the authors use shallow WGS to create machine learning signatures to identify tumor phenotypes and predict therapy response in patients with metastatic breast cancer.